Fitomasa subterránea en pastizales semiáridos de dehesa. Estudio comparativo de cuatro transecciones - Gomez Gutiérrez, J M; BARRERA MELLADO, I; FERNÁNDEZ SANTOS, B; Guti, M E Z; Mellado, Barrera; Santos, Ndez (Pastos, 1988)
A comparative study of the underground phytomass (roots) valúes obtained along four transverse sections of four water courses was made in some semiarid grasslands, that are representative of the Central- Western área of Spain (Provinces of Avila and Salamanca). In order to perform this study, the following item's were studied: a) the total phyto- mass valúes for each profile (30 cm depth, 9 cm diameter), b) the hori- zons or 5 cm horizontal transect, in each section, c) the samples in each profile. Very similar sequences were observed in all the transects, high- lighting the effect of relief on underground phytomass, wich is considered a synthesis and an expression of the edaphicclimatic and anthropozoogenic action that governs its development. Key
Keywords: fitomasa subterránea; Grasslands; pastizales; raíces; roots; vaguada; water course